The Effect of Employee Engagement, Employee Retention and Turnover Intention on Employee Performance in Dinas Pendidikan Kabupaten Labuhanbatu - Retno Shinta Dewi; Junita Lubis; Meisa Fitri Nasution (Budapest International Research and Critics University, 2022)
This research was conducted at the Education Office of Labuhanbatu Regency, with the aim of analyzing the effect of employee engagement, employee retention, and turnover intention on employee performance. The results of the study indicate that all independent variables have a positive and significant effect on the dependent variable, either partially or simultaneously. This can be proven through the t test and F test.The results of the t test can be described as follows, the employee engagement variable has a tcount value of 4.95 > a ttable value of 1.66 which means Ha is accepted and Ho is rejected, with a significance value of 0.000 < probability value of 0.05, it can be concluded that the employee engagement variable (X1) has a positive and significant effect on employee performance (Y). Employee retention variable has a tcount value of 2.57 > ttable value 1.66 which means Ha is accepted and Ho is rejected, with a significance value of 0.012 < probability value of 0.05, it can be concluded that the employee retention variable (X2) has a positive and significant effect on employee performance. (Y). The turnover intention variable has a tcount value of 12.86 > a ttable value of 1.66 which means Ha is accepted and Ho is rejected, with a significance value of 0.000 < probability value 0, 05, it can be concluded that the variable turnover intention (X3) has a positive and significant effect on employee performance (Y). While the F test in this study has an Fcount of 97.21 > Ftable 2.70 with a significance value of 0.000 <0.05. Based on these results, it can be stated that employee engagement, employee retention and turnover intention are simultaneously able to have a positive and significant impact on employee performance.